IL-6 blockade in systemic juvenile idiopathic arthritis: achievement of inactive disease and remission (data from the German AID-registry) - Bielak, Maria; Lutz, Thomas (Pediatric rheumatology, 2018)
Systemic juvenile idiopathic arthritis (sJIA) is a complex disease with an autoinflammatory component of unknown etiology related to the innate immune system. A major role in the pathogenesis has been ascribed to proinflammatory cytokines like interleukin-6 (IL-6), and effective drugs inhibiting their signaling are being developed. This study evaluates sJIA patients treated with the IL-6 inhibitor tocilizumab (TCZ) concerning clinical response rate, disease course and adverse effects in a real-life clinical setting.